2016
DOI: 10.22211/cejem/62349
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Induced Polymorphic Transformation of Hexanitrohexaazaisowurtzitane (HNIW) Investigated by in-situ X-ray Powder Diffraction

Abstract: Abstract:The ε→γ phase transition of HNIW induced by heat was investigated with in situ X-ray powder diffraction (PXRD). The effects of purity, particle size, insensitive additives and the time of isothermal heat treatment on the phase transition were evaluated. It was found that the phase transition is irreversible with changes in temperature, and the two phases can coexist in a certain temperature range. Moreover, the initial phase transition temperature increases with increasing purity and decreasing partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…Liu et al pointed out that the PT of the ε → γ forms of CL-20 has a relation to the purity and particle size of the sample. 77 As demonstrated in Figure 4, the initial temperature of PT increases with an increase in the purity or decrease in the particle size. Usually, a smaller size with a higher specific surface facilitates an easier PT with a lower transition temperature.…”
Section: Factors Influencing the Polymorphicmentioning
confidence: 90%
See 2 more Smart Citations
“…Liu et al pointed out that the PT of the ε → γ forms of CL-20 has a relation to the purity and particle size of the sample. 77 As demonstrated in Figure 4, the initial temperature of PT increases with an increase in the purity or decrease in the particle size. Usually, a smaller size with a higher specific surface facilitates an easier PT with a lower transition temperature.…”
Section: Factors Influencing the Polymorphicmentioning
confidence: 90%
“…Liu et al also reported that additives with different inertia can influence the ε → γ PT of CL-20. 77 The initial PT temperature decreases with an increase in the contents of graphite and paraffin wax, while it does not change by adding TATB. Also, Thallapally et al reported that the PT of 1,3,5-trinitrobenzene (TNB) is promoted by adding trisindane (TI).…”
Section: Factors Influencing the Polymorphicmentioning
confidence: 96%
See 1 more Smart Citation
“…(2) Additives are incorporated via conventional coating or physical mixing to investigate the phase transformation of ε-CL-20 crystals. The additives usually have a high dipole moment or slightly dissolve CL-20, which can easily polarize ε-CL-20, thus promoting its transition to γ-CL-20 [15,16]. Neutral polymers, such as glycidyl azide polymer (GAP), isocyanate desmodur (N100), ethylene propylene diene monomer (EPDM), and butadiene rubber (BR), inhibit the crystal change of CL-20 [6,17].…”
Section: Introductionmentioning
confidence: 99%
“…An explosive crystal undergoes many complex physical processes during its polymorphic transformations, which includes a change in the molecular structure, symmetries and molecular stacking patterns, etc. Usually, X-ray diffraction is adopted as the standard method for the study of polymorphic transformations, 8,9 which provides the geometric structure of the molecular crystal. However, this is difficult in the present circumstance since the polymorphic transformations involve a dynamic motion; this important factor reveals the performance and packing sensitivity of the crystalline explosive.…”
Section: Introductionmentioning
confidence: 99%